“Crossroads. The Game of your Life”: the Development of a Playful tool to Prevent Cancer - Maia, Tainá (2013)
Introduction: According to the National Cancer Institute José Alencar Gomes da Silva, about 80% of cancers are related to the environment. Annually applied researches performed by the Brazilian Institute for Geography and Statistics, across the entire national territory, confirm that a large number of teenagers expose themselves to those factors. Other studies show an almost complete lack of knowledge among adolescents in relation to cancer and risk factors associated with the development of the disease. Objective: to describe the creation and evaluation of a playful product of entertainment to clarify young people about the importance of cancer prevention. Method: We developed a role-playing game book titled “Encruzilhadas. O jogo da sua vida” (Crossroads. The game of your life). We evaluated its use as an alternative educational tool by applying the technique of focus groups. Results: The book contains 332 references that narrate common situations on the routine of young people, highlighting the various moments when they are exposed to risk factors for cancer. To evaluate the effectiveness of this instrument, we conducted six focus groups with young people from a public school in Rio de Janeiro. Conclusion: The evaluation showed that the developed material is able to arouse questioning about cancer, risk factors and ways of prevention among the young people, besides the fact that the book helps in the understanding and assimilation of the content shown.